A Post-Synthetic Modification Strategy for the Preparation of Homooligomers of 3-Amino-1-methylazetidine-3-carboxylic Acid - Liu, Dayi; Imani, Zeynab; Gourson, Catherine; Guillot, Régis; Robin, Sylvie; Aitken, David J. (Synlett, 2023)
Post-synthetic modification is a powerful technique allowing access to noncanonical peptide derivatives in a selective manner, but it has not so far been applied for the installation of multiple arrays of modified side chains. Here, we use this approach in solution phase to prepare short N- and C-capped homooligomers of 3-amino-1-methylazetidine-3-carboxylic acid with all the azetidine side chain functions in free amine form. The key step is the multiple reductive amination reaction of the corresponding post-synthetically deprotected secondary amines.
Keywords: azetidines; late-stage modification; peptides; reductive amination; protected amino acid; oligomers